Homeopathic Treatment of Subclinical Hypothyroidism—A Series of 19 Cases - Grelle, Luiz Carlos Esteves; Camacho, Luiz Antonio Bastos (Homeopathy, 2021)
Background Subclinical hypothyroidism (SCH) is a common clinical problem. Controversy surrounds the definition, clinical importance, and need for prompt diagnosis and treatment of the mild form of SCH.Aim The aim of the study was to analyze the evolution of serum thyroid stimulating hormone (TSH) levels after a therapeutic homeopathic intervention in women older than 40 years with SCH.Methods This study is a retrospective series of 19 cases of SCH, with serum TSH levels between 5 and 10 mIU/L, treated exclusively with homeopathic medicines prescribed on an individualized basis.Results Nineteen patients were included according to the inclusion and exclusion criteria. Their mean age was 56 years, they were followed for a mean duration of 69 months, the mean number of serum TSH level measurements was 18, and the intervention was successful for 13 patients.Conclusion The homeopathic therapeutic intervention was successful in 68% of the patients, with serum TSH levels back within the normal range (0.5–5.0 mIU/L).
Keywords: mild thyroid failure; individualized homeopathy